Internal Governance and Real Earnings Management - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2013)
We examine whether internal governance affects the extent of real earnings management. Internal governance refers to the process through which key subordinate executives provide checks and balances in the organization and affect corporate decisions. Using the number of years to retirement to capture key subordinate executives’ incentives and using their compensation relative to CEO compensation to capture their influence within the firm, we find that the extent of real earnings management decreases with key subordinate executives’ horizon and influence. In cross-sectional analyses, we find that the impact of internal governance is more important for firms with more complex operations where key subordinate executives’ contribution is higher, is enhanced by the effectiveness of other governance mechanisms, and is stronger in the post-SOX period, when real earnings management is likely more prevalent. The results are also robust to controlling for potential endogeneity concerns and to using alternative measures of internal governance. This paper contributes to the literature by examining how internal governance affects the extent of real earnings management and by shedding light on how the members of the management team work together in shaping financial reporting quality.